Learning Software Application Design Model for Children with Cerebral Palsy (International Journal of Innovative Computing, 2014)
Most of the software applications for children with cerebral palsy (CP) do not focus on learning issues. This paper describes a study of learning issues for children with cerebral palsy and their requirements. The findings are translated into a Learning Software Application Design Model (LSAM), which could be used in developing other types of learning software application for children with CP. Guidelines for designing and developing a learning prototype that are compatible with the limited capabilities of children with CP are planned to ensure they are able to grasp the concepts of a learning software application prototype. The prototype is developed using a game application and also a GlovePie Tool. We present discussion on the learning software application design model that used for designing and developing the game learning application prototype.